Experiences of seeking healthcare across the border: lessons to inform upstream policies and system developments on cross-border health in East Africa - Leon Mutesa; Freddie Ssengooba; Aloysius Ssennyonjo; Doreen Tuhebwe; Steven Ssendagire; Susan Babirye; Martha Akulume; Arthur Rutaroh; Mabel Nangami (BMJ Open)
Objectives This study explored the experiences of accessing care across the border in East Africa.Participants From February to June 2018, a cross-sectional study using qualitative and quantitative methods was conducted among 279 household adults residing along selected national border sites of Uganda, Kenya and Rwanda and had accessed care from the opposite side of the border 5 years prior to this study.Setting Access to HIV treatment, maternal delivery and childhood immunisation services was explored. We applied the health access framework and an appreciative inquiry approach to identify factors that enabled access to the services.Measures Exploratory factor analysis and linear regression were used for quantitative data, while deductive content analysis was done for the qualitative data on respondent’s experiences navigating health access barriers.Results The majority of respondents (83.9%; 234/279) had accessed care from public health facilities. Nearly one-third (77/279) had sought care across the border more than a year ago and 22.9% (64/279) less than a month ago. From the linear regression, the main predictor for ease of access for healthcare were ‘‘ease of border crossing’ (regression coefficient (RegCoef) 0.381); ‘services being free’ (RegCoef 0.478); ‘services and medicines availability’ (RegCoef 0.274) and ‘acceptable quality of services’ (RegCoef 0.364). The key facilitators for successful navigation of access barriers were related to the presence of informal routes, speaking a similar language and the ability to pay for the services.Conclusion Communities resident near national borders were able to cross borders to seek healthcare. There is need for a policy environment to enable East Africa invest better and realise synergies for these communities. This will advance Universal Health Coverage goals for communities along the border who represent the far fang areas of the health system with multiple barriers to healthcare access.